2017
DOI: 10.1097/ta.0000000000001357
|View full text |Cite
|
Sign up to set email alerts
|

Damage control laparotomy utilization rates are highly variable among Level I trauma centers

Abstract: Background Damage control laparotomy (DCL) is intended to limit deleterious effects from trauma induced coagulopathy. DCL has been associated with mortality reduction, but may increase complications including sepsis, abscess, respiratory failure, hernia, and gastrointestinal fistula. We hypothesized that (1) DCL incidence would vary between institutions; (2) mortality rates would vary with DCL rates; (3) standard DCL criteria of pH, INR, temperature and major intra-abdominal vascular injury (MVI) would not ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…A major asset in the treatment of a trauma patient is knowledge of damage control concepts. Damage control surgery (DCS) can be performed in severely injured patients as part of the resuscitation process [12]. In DCS, the goal is to reduce operating time as much as possible, preferably within 1-1.5 h, in which hemorrhage and contamination is controlled, while additional damage is prevented [13].…”
Section: Introductionmentioning
confidence: 99%
“…A major asset in the treatment of a trauma patient is knowledge of damage control concepts. Damage control surgery (DCS) can be performed in severely injured patients as part of the resuscitation process [12]. In DCS, the goal is to reduce operating time as much as possible, preferably within 1-1.5 h, in which hemorrhage and contamination is controlled, while additional damage is prevented [13].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the above data suggest that there exists little evidence to support the high DC surgery utilization rates reported by many level 1 trauma centers. In a recently reported post-hoc analysis of the PROPPR randomized trial, DC was used among 33-83% of patients requiring urgent laparotomy across 12 of the participating institutions [15]. Interestingly, although there was no signi cant adjusted mortality difference between these centers, the unadjusted risk of sepsis and ventilator-associated pneumonia was higher among those treated with DC laparotomy, suggesting that decreasing use of DC among individual trauma centers may not in uence mortality, but may decrease associated morbidity [15].…”
Section: Narrative Synthesis Of Validity Of Indications For Use Of DCmentioning
confidence: 99%
“…It is therefore important to ensure that DC surgery is only performed on patients in which the expected survival bene t of the procedure outweighs its expected risk of negative consequences [1]. Despite this, the bene t/risk pro le of using DC surgery in different clinical situations has not been comprehensively evaluated, and several authors have recently reported data suggesting that substantial variation in use of DC surgery exists across trauma centers or that it may be overused [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In sum, the DCS approach should be applied in the presence of the previously described prognosis factors, and the surgical management strategy must be based on the dynamic response to resuscitation rather than the patient physiology indicators or injury characteristic at the presentation. Due to the absence of high-level evidence data regarding the appropriate indications, a recent report (2017) highlighted the inconsistent use of the DCS approach with signifi cant variation across tertiary trauma centres [46]. However, the damage control strategy remains primordial in the management of shocked patients or those not responding to intensive resuscitation.…”
Section: Damage Control Surgery Indications and Current Evidence Datamentioning
confidence: 99%